Correction: Desterke et al. Alternative Balance between Transcriptional and Epigenetic Regulation during Developmental Proliferation of Human Cranial Neural Crest Cells. Cells 2024, 13, 1634 - Desterke, Christophe (2025)
In the original publication [1], the funder “MEAE AMBASS FRANCE AU PEROU FSPI—S-AC23007, Filière Santé Maladie Rare «TeteCou-CRANIOST»” must be modified by “This research received no external funding” due to the fact that, since it is a computationaldeveloped article, the use of funds was not necessary.